Federation of Australia. - World Book, Inc. (Chicago World Book, 2011)
"A history of the settlement and founding of Australia, based on primary source documents and other historical artifacts. Features include period art works and photographs; excerpts from literary works, letters, speeches, broadcasts, and diaries; summary boxes; a timeline; maps; and a list of additional resources"--Provided by publisher.
Arrival in Australia -- Free settlers -- Aborigines and European settlers -- The gold rush -- The Eureka Stockade -- New South Wales and Tasmania -- Victoria and South Australia -- Queensland and Western Australia -- Linking the colonies -- The crisis of the 1890's -- Australian nationalism -- The federal idea -- The Federal Council -- Sir Henry Parkes -- The 1890 Conference -- What form of federation? -- The First Federal Convention -- The people's conventions -- New Zealand stays out -- The Second Federal Convention -- The referendums -- The United Kingdom approves -- The birth of a nation -- The first national elections -- The new parliament -- Sir Edmund Barton -- Voting rights for women -- A new capital.
Keywords: Australia -- History -- Juvenile literature; Australia -- History -- Sources -- Juvenile literature; Australia -- Politics and government -- Juvenile literature